2010
DOI: 10.1073/pnas.1004623107
|View full text |Cite
|
Sign up to set email alerts
|

Thymopoiesis in mice depends on a Foxn1 -positive thymic epithelial cell lineage

Abstract: The thymus is essential for T-cell development. Here, we focus on the role of the transcription factor Foxn1 in the development and function of thymic epithelial cells (TECs) of the mouse. TECs are of endodermal origin; they initially express Foxn1 and give rise to orthotopic (thoracic) and additional (cervical) thymi. Using Foxn1-directed cytoablation, we show that during embryogenesis, cervical thymi develop a few days after the thoracic lobes, and that bipotent epithelial progenitors of cortical and medulla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
132
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(141 citation statements)
references
References 30 publications
9
132
0
Order By: Relevance
“…The early "ubiquitous" expression of Foxn1 in the developing thymus is in line with the reported fate-mapping data (37,38). We addressed the origin of the few Foxn1 2 TECs in embryonic mice.…”
Section: Discussionsupporting
confidence: 60%
“…The early "ubiquitous" expression of Foxn1 in the developing thymus is in line with the reported fate-mapping data (37,38). We addressed the origin of the few Foxn1 2 TECs in embryonic mice.…”
Section: Discussionsupporting
confidence: 60%
“…42,43,48 Our results clearly indicate that Wnt4 regulates the number of TECs in the thymus and consequently the number of intrathymic niches available for thymus-seeding progenitors ( Figures 4A, 5A, and 6). Conversely, Wnt4 also is capable of directly influencing the expansion of the most immature cKit hi thymocytes in vitro ( Figure 3C-D).…”
Section: Discussionmentioning
confidence: 60%
“…Several investigators have also shown that, in addition to maintain existing TECs, FOXN1 also regulates TEC progenitors [15,16,18,27,31], which may also contribute to the increased number of TECs. The number of ETPs was also significantly increased after rFOXN1 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…FOXN1 is required not only for TEC development in fetal thymus, but also for maintenance of the postnatal thymus [15,16,23,24,26]. The reduced expression or induced deletion of FOXN1 resulted in reduced TEC number and a disrupted thymic microenvironment [16,18,22,24,27]. Conversely, an intrathymic injection of FOXN1 cDNA-bearing plasmid into the thymus of aged mice or FOXN1 transgenic mice resulted in an increased number of TECs, leading to enhanced thymopoiesis and an increased naïve T-cell output [23,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation